PERUBAHAN KERAPATAN VEGETASI DAERAH ALIRAN SUNGAI BODRI BERDASARKAN INTERPRETASI CITRA PENGINDERAAN JAUH - Sanjoto, Tjaturahono Budi (Jurnal Geografi, 2013)
This study aims to assessing changes in watershed vegetation density in multitemporalBodri (1992-2009) with remote sensing satellite imagery. This researchis descriptive-eksplanatory. Research variables include changes in vegetationdensity on the watershed Bodri (1992-2009). The results showed that thevegetation density of Bodri watershed began in 1992, 2002, and 2009 may changerelatively dynamic and each category is different. Tightly categories grew wide,otherwise meeting the more narrow category. This indicates that reforestation bedone in the upstream watershed Bodri progressing well.